ASSOCIAÇÃO ENTRE A ESPESSURA DIAFRAGMÁTICA E DESEMPENHO FÍSICO DE ATLETAS E OS EFEITOS DA INFECÇÃO POR COVID-19: UM ESTUDO TRANSVERSAL - ALLINY SOUZA FARIAS (2022)
Studies carried out in healthy patients and individuals suggest that diaphragm hypertrophy, that is, an increase in the cross-sectional area, can result in greater inspiratory muscle strength, consequently better ventilatory and mechanical efficiency. On the other hand, infectious diseases such as COVID-19 can impact the structure and function of the respiratory system. However, there are still few studies that have evaluated the diaphragm thickness of athletes, how it is associated with physical performance and the impacts of COVID-19 on these outcomes. Therefore, the purpose of this study was to evaluate the association between diaphragm thickness and physical performance of athletes and the effects of COVID-19 infection on these parameters. This is a cross-sectional study, involving 63 athletes from different sports of both sexes (Female 16,67±5,03y, 52,09±14,01kg, 155,90±13,86cm; Male 23,44±9,65y, 72,24±14,18kg, 174,84±6,84 cm), which were submitted to evaluation of diaphragmatic thickness by ultrasound and then to the aerobic performance test (YoYo test) for VO2max determination. For statistical analysis, Pearson's correlation was used to verify the association between VO2max and diaphragmatic thickness and Student's t test was applied to verify differences between athletes with a positive and negative diagnosis for COVID-19. The significance level was set at 5%. There was no association between diaphragmatic thickness and physical performance (r=0.30 and p=0.22) and no difference between uninfected and COVID-19 infected athletes in relation to diaphragmatic thickness (57.00±0.26 vs 52.00 ±0.25; p=0.22) and physical performance (43.88±2.29 vs 38.34±13.61mL/kg/min; p=0.22), respectively. Conclusion: In athletes, diaphragmatic thickness was not associated with maximal oxygen consumption. In addition, athletes infected by COVID-19 did not exhibit differences in VO2max and diaphragmatic thickness, in relation to uninfected athletes.